적층 제조형 방식의 3D 프린터로 제작한 뇌 팬텀의 유용성 - 이용기(Lee Yong-Ki), 안성민(Ahn Sung-Min) (방사선기술과학, 2020)
The price of the Brain phantom (Hoffman 3D brain phantom) used in nuclear medicine is quite expensive, it is difficult to be purchased by a medical institution or an educational institution. Therefore, the purpose of present research is to produce a low-price 3D brain phantom and evaluate its usefulness by using a 3D printer capable of producing 3D structures. The New 3D brain phantom consisted of 36 slices 0.7 mm thick and 58 slices 1.5 mm thick. A 0.7 mm thick slice was placed between 1. 5 mm thick slices to produce a composite slice. ROI was set at the gray matter and white matter scanned with CT to measure and compare the HU, in order to verify the similarity between PLA which was used as the material for the New 3D brain phantom and acrylic which was used as the material for Hoffman 3D brain phantom. As a result of measuring the volume of each Phantom, the error rate was 3.2% and there was no difference in the signal intensity in five areas. However, there was a significant difference in the average values of HU which was measured at the gray and white matter to verify the similarity between PLA and acrylic. By reproducing the previous Hoffman 3D brain phantom with a 100 times less cost, I hope this research could contribute to be used as the fundamental data in the areas of 3D printer, nuclear medicine and molecular imaging and to increasing the distribution rate of 3D brain phantom.